Crypto-Egalitarian Life: Ideational and Materialist Approaches to Bitcoin. - Shapiro, Matan (Social Analysis, 2022)
In this article I explore the fundamental tension in the world of Bitcoin between 'maximalists', who see Bitcoin as a tool for the promotion of a moral revolution, and 'traders', who approach Bitcoin pragmatically as a financial tool. Based on ethnography of a crypto gold rush that took place in the Bitcoin Embassy in Tel Aviv, I argue that, despite heuristic distinctions, both of these attitudes advance egalitarian tendencies. While maximalists offer a sense of belonging to a close-knit community of equals, traders promote the nominal equality of all value-making strategies in an open financial environment. I use the terms 'ideational' and 'materialist' to characterize these two modes of practice, which realize contemporary visions of egalitarian life in different forms.